On the Second Descent Points for the K-Error Linear Complexity of 2(n)-Periodic Binary Sequences - Zhou, J.; Wang, X.; Liu, Wan-Quan (2016)
In this paper, a constructive approach for determining CELCS (critical error linear complexity spectrum) for the kerror linear complexity distribution of 2n -periodic binary sequences is developed via the sieve method and Games-Chan algorithm. Accordingly, the second descent point (critical point) distribution of the k-error linear complexity for 2n -periodic binary sequences is characterized. As a by product, it is proved that the maximum k-error linear complexity is 2n -(2l -1) over all 2n -periodic binary sequences, where 2l-1<=k < 2l and l < n. With these results, some work by Niu et al. are proved to be incorrect.